Characterization of Persistent Modoc Viral Infections in Syrian Hamsters - Davis, James W. (1974)
Adult Syrian hamsters were readily infected by intranasal inoculation with Modoc virus. Viremias were detected 2 to 6 days after infection and peak viremia titers (10(6.2) plaque-forming units/ml of blood) occurred 4 days postinoculation. All infected animals developed neutralizing and hemagglutination-inhibiting antibodies by 7 days, and complement-fixing antibodies by 14 days postinoculation. High titers of antibodies persisted for at least 4 months. Modoc virus was recovered from throat swabs at 7 days postinoculation, but not at 14 days or later. Urine samples were positive for virus throughout a 12-week observation period. Isolation of virus from lungs and kidneys of one and three animals, respectively, at 151 to 221 days after inoculation confirmed chronic infection. Viral isolations were made only when organs were cultivated in vitro and were unsuccessful by tests on 10% homogenates of the organs. Horizontal viral transmission of virus by infected hamsters that were viruric was demonstrated in only 1 of 27 normal hamsters that were cocaged for 4 weeks under crowded conditions. General failure to obtain horizontal viral transmission may relate to rapid inactivation of virus in excreted urine. Vertical viral transmission was not demonstrated from five chronically infected female hamsters to their 34 offspring. However, if primary infection occurred during pregnancy, the progeny were either stillborn or died shortly after birth, and thus appeared to represent transplacental viral transmission.